Phytosociological Studies of the Vegetation of Saurashtra (Gujarat) 4. Ordination of Localities - Menon, A. R. R.; Shah, G. L. (Indian Forester, 1981)
To suppliment the Phytosociology of the vegetation of Saurashtra in Gujarat, India, the Maturity Index, (Pichi-Sermolli, 1948) Community Coefficient (Soresen, 1948) etc. of 20 localities of Gir forests are studied. Most of the localities are moderately mature. The Community Coefficient values are categorised into different classes as per their frequency distribution and most of the combinations of mutual comparisions falls within the range of 41-60% similarity and the percentage of extermity at both ends are very less. Also an attempt is made to ordinate the dissimilarity value by using multipolar Ordination Technique (Bray and Curtis, 1957) and a graphic representation of different localities are made. The values are further tested by using standard statistical indices with known probability distribution and the method seems to be satisfactory for the present study.